Understanding crowdfunding as collaborative networks for startups: A research agenda - Telles, Renato; Goes, Weslei Meireles de; Ferreira, Gabriel Gomes; Zenke, Adriane Akemi; Ferraro, Rosangela (REGEPE Entrepreneurship and Small Business Journal, 2024)
Objective: To contribute to the expansion of crowdfunding strategies' efficiency by incorporating the perspective of a collaborative network in financing the startup's initial operation. The study focused on investigating crowdfunding as a network with a collaborative culture and management. Methodology: A literature review was conducted to identify conceptual convergences between crowdfunding and collaborative networks. The aim was to assess the potential improvement of crowdfunding strategies by understanding the process as a collaborative network. Relevance/Originality: The article presents an innovative and additional approach to crowdfunding strategy by conceptualizing and operationally supporting its design and management as a collaborative network. Results: The study provides a consistent conceptual comparison between crowdfunding and collaborative network dimensions, identifying the theoretical convergence between the two. As a result, it indicates the viability of collaborative networks as a relevant theoretical contribution to building and managing crowdfunding campaigns. Theoretical and Methodological Contributions: The research offers (a) consistent evidence of conceptual compatibility between the studied constructs and (b) proposes a research agenda with potential research questions for future studies based on the convergence between crowdfunding for startups and collaborative networks.